Efektivitas Program Pencegahan Stunting Di Puskesmas Medan Tuntungan - Lubis, Irwansyah; Salsabila, Rizka Fauziah; Rahma, Putri Aulia; Pulungan, Dea Rizka Ananda; Fahny, Vira Zul; Nazli, Amanda Husnatul; Ritonga, Aprida Khairani (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Stunting is a serious global public health problem, especially in developing countries like Indonesia, because its prevalence is still relatively high. This study aims to evaluate the effectiveness of the stunting prevention program at the Medan Tuntungan Health Center. Through a qualitative-descriptive approach, this study collected data through interviews with the Head of the Stunting Prevention Program, cadres, and the local community. The results show that this program is able to reduce stunting rates significantly, although there are still challenges such as social stigma from parents regarding their children's stunting status and limited funds for the provision of nutritional assistance. Cross-sector collaboration, community participation, and cadre dedication are very important in increasing public awareness and understanding of the importance of nutrition for children. It is hoped that with continued support, this program can contribute more to reducing the prevalence of stunting in the future.